Vivendo com vitiligo: variáveis psicossociais e representações simbólicas - Sacramento, Augusta Renata Almeida do (2012)
This paper was aimed at observing the psychosocial variables resulting from vitiligo and symbolic representations of such a disease. Sixty women, aged between 19 and 77 have participated of this study. Thirty out of all of them had vitiligo (experimental group) and other 30 had different skin diseases (control group). The following instruments were used to collect data: #1 Form to characterization of sample, #2 Dermatology Life Quality Index (DLQI), #3 Semi-structured interview and #4 Theme drawing. The DLQI was applied in the two groups and the other instruments applied only in experimental group. The data collected were analyzed under analytical psychology and psychosomatic Jungian. The interviews speeches were analyzed, then 03 categories and 10 subcategories were determined: emotional factors (factors which caused the disease, aggravating factors of the disease); the disease purpose; living with the disease (social support, prejudice, disturbances derived from the disease, behavior towards the disease, the disease impact, exposition to the symptoms, expectations concerning the treatment and fear of kids having the disease). The results revealed a commitment to the life quality not only to the women having vitiligo but also to the women who had other skin diseases, and there was no significant statistical difference between the two groups. It was observed the association of emotional aspects in the appearance and/or aggravating condition of vitiligo as well as behavioral changes, limitations and prejudice experienced by women having the disease. The drawings pointed out certain symbolic representations of vitiligo, showing conflicts and suffering due to the disease